HS1BP3 negatively regulates autophagy by modulation of phosphatidic acid levels - Petter Holland (Nature Portfolio, 2016)
Autophagy must be tightly controlled at each step of the process. Here the authors show that HS1BP3 binds phosphatidic acid (PA) at autophagosome precursors and negatively regulates autophagosome formation by modulating the activity and localization of the PA-producing enzyme phospholipase D1.